A new method to characterize low stopping power and ultra-fast scintillators using pulsed X-rays - Pagano, Fiammetta; Kratochwil, Nicolaus; Frank, Isabel; Gundacker, Stefan; Paganoni, Marco; Pizzichemi, Marco; Salomoni, Matteo; Auffray, Etiennette (Frontiers in Physics, 2022)
The demand for detectors with a time resolution below 100 ps is at the center of research in different fields, from high energy physics to medical imaging. In recent years, interest has grown in nanomaterials that, benefiting from quantum confinement effects, can feature ultra-fast scintillation kinetics and tunable emission. However, standard characterization methods for scintillation properties – relying on radiation sources with an energy range of several hundreds of keV – are not suitable for these materials due to their low stopping power, leading to a slowdown of this R&D line. We present a new method to characterize the time resolution and light output of scintillating materials, using a soft (0-40 keV energy) pulsed X-ray source and optimized high-frequency readout electronics. First, we validated the proposed method using standard scintillators. Then, we also demonstrate the feasibility to measure the time resolution and get an insight into the light output of nanomaterials (InGaN/GaN multi quantum well and CsPbBr3 pervoskite). This technique is therefore proposed as a fundamental tool for the characterization of nanomaterials and, more in general, of materials with low stopping power, to better guide their development. Moreover, it opens the way to new applications where fast X-ray detectors are requested, like Time-of-Flight X-ray imaging.